Effect of plasma treatment on mechanical and thermal properties of marble powder/epoxy composites. Issue 2 (29th January 2016) - Fiore, V.; Di Bella, G.; Scalici, T.; Valenza, A.
Abstract : The aim of this work was to study the effect of the plasma treatment on the behavior of composite structures reinforced with marble powder, obtained as processing waste in the "Custonaci" basin. Moreover, different filler amounts (i.e., 10%wt, 20%, 30% in weight) were investigated. For the mechanical characterization, tensile and flexural quasi‐static tests, Charpy impact test, and dynamic mechanical thermal analysis (DMTA) were performed. For the thermal stability, thermogravimetric analysis was carried out. Finally, real density and fraction of voids were measured. It was observed that untreated marble powder, on one hand, increases tensile and flexural stiffness and improves thermal stability, on the other hand, introduces a defectivity that produces a decrease of some properties (i.e., ultimate tensile and flexural strength). The plasma treatment induces improvements in all the mechanical properties (i.e., quasi‐static and dynamic). Vice versa, the thermal behavior is not affected by the treatment. POLYM. COMPOS., 39:309–317, 2018. © 2016 Society of Plastics Engineers